How to improve the competiveness of natural gas in China with Energy Internet and "The Belt and Road Initiative". (15th August 2018) - Hou, Jianchao; Wang, Che; Liu, Pingkuo
Summary: To enhance the competitiveness of natural gas is an urgent requirement for China's economy development. "The Belt and Road Initiative, " aiming to achieve win‐win situation with other countries along the route, was proposed in 2013, which is a great opportunity for the development of natural gas. And the rise of Energy Internet has infused great vitality into the development of natural gas by technological innovation. This paper first reviews the current status of China's natural gas industry and further analyzes the policy status for the development of natural gas. Then, through the policy, economy, society, and technology‐strengths, weaknesses, opportunities, and threats analysis, this paper reveals the internal strengths and weaknesses as well as external opportunities and challenges of promoting China's natural gas development. Then this paper analyzes approaches of The Belt and Road Initiative and Energy Internet to promote the role of natural gas development and put forward the relevant construction steps. Finally, this paper puts forward the corresponding research conclusions and policy suggestions for the development of natural gas industry. Abstract : In this paper, current situation of natural gas industry in China is investigated. The impact of "The Belt and Road Initiative" on natural gas industry in China and how Energy Internet can promote the development of natural gas industry in China is studied. The suggestion of improving the competiveness of natural gas in China is proposed.